2022
DOI: 10.3390/pharmaceutics14081555
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in VEGFR Coding Genes (FLT1/KDR) on Ranibizumab Response in High Myopia and Choroidal Neovascularization Patients

Abstract: A severe form of myopia defined as pathologic/high myopia is the main cause of visual impairment and one of the most frequent causes of blindness worldwide. It is characterized by at least 6 diopters or axial length (AL) of eyeball >26 mm and choroidal neovascularization (CNV) in 5 to 10% of cases. Ranibizumab is a humanized recombinant monoclonal antibody fragment targeted against human vascular endothelial growth factor A (VEGF-A) used in the treatment of CNV. It acts by preventing VEGF-A from interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Ma et al had already identified in 2007 that five SNPs in this gene were associated with significant changes in HbF (% and g/dL) [14]. Previous studies have already found significant associations with this specific variant (rs7993418) and the response to ranibizumab [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…Ma et al had already identified in 2007 that five SNPs in this gene were associated with significant changes in HbF (% and g/dL) [14]. Previous studies have already found significant associations with this specific variant (rs7993418) and the response to ranibizumab [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…SNP in the metabolizing genes ( CYP3A4 , CYP3A5 , CYP2B6 , POR , and NR1I2 ) and the transporter family genes ( SLC22 , SLC19 , SLCO , and ABC ) were genotyped with an SNP mass array platform. Angiogenesis-related genes ( VEGFA , VEGFR2/KDR ), cytokine receptor gene ( IL4R ), and epidermal growth factor receptor gene ( EGFR ) were also analyzed ( 12 - 14 ). We present this article in accordance with the REMARK reporting checklist (available at https://jgo.amegroups.com/article/view/10.21037/jgo-24-188/rc ).…”
Section: Introductionmentioning
confidence: 99%
“…Although anti-vascular endothelial growth factor (VEGF) therapy has replaced photodynamic therapy, pmCNV remains an urgent challenge for low responders and a burden for patients who need multiple treatments or among patients with severe myopic maculopathy [5,6]. Remarkably, the efficacy of anti-VEGF drugs, such as ranibizumab, may depend on genetic polymorphisms, in which FLT1 (rs9582036, rs7993418) variants may serve as a genetic marker [7]. In fact, other risk factor, including the presence of perforating scleral vessels or macular Bruch membrane breakdown, may hinder the response to anti-VEGF therapy as well [8,9].…”
Section: Introductionmentioning
confidence: 99%